Post-harvest processing methods have critical roles on the contents of active metabolites and pharmacological effects of Astragali Radix - Xiaoyan Zhang; Shengnan Jiang; Tingting Sun; Wenbing Zhi; Kairu Ding; Ziyao Qiao; Hong Zhang; Hong Zhang; Ye Li; Yang Liu; Yang Liu (Frontiers in Pharmacology)
BackgroundProcessing methods of traditional Chinese medicinal materials are critical in influencing the active metabolites and pharmacological effects. The fresh processing method effectively prevents the loss and degradation of metabolites, common in traditional drying and softening processes, while also reducing production costs. Astragali Radix (AR), a leguminous botanical drug, is widely utilized in clinical practice and functional foods. Therefore, optimizing its the post-harvest processing method is crucial for enhancing production and application.MethodsAR samples were processed using different methods with varying moisture content, including unpretreated samples and those subjected to kneading and sweating treatments. These samples were evaluated for physical appearance and active metabolite content. The entropy weight method, combined with the technique for order preference by similarity to ideal solution (TOPSIS), was employed to optimize the fresh processing method. A comparative study between freshly processed AR (AR-F) and traditionally processed AR (AR-T) assessed active metabolites, pharmacological effects and mechanisms.ResultsThe appearance and active metabolites content of AR samples were affected by moisture content, kneading, and sweating treatments. After these treatments, the content of polysaccharides and calycosin-7-O-glucoside increased compared to unpretreated samples at the same moisture level. Entropy weight-TOPSIS analysis showed that the sample with 35% moisture, 100 kneading cycles, and 12 h of sweating had the highest score. Comparative studies revealed that AR-F had significantly higher content of total polysaccharides, total flavonoids, and calycosin-7-O-glucoside compared to AR-T, along with an increased flavonoid glycoside/aglycone ratio. However, no significant differences were observed in the total saponins and their metabolites. Pharmacological studies demonstrated that total flavonoids in AR-F exhibited superior macrophage RAW264.7 activation, compared to AR-T. Furthermore, we confirmed that the enhanced immunomodulatory capacity of AR-F was linked to its ability to stimulate the release of TNF, SRC, ER-α, AKT, HSP90, and Caspase-3 in RAW264.7 cells.ConclusionOur study optimized the fresh processing method of AR, and conducted a systematic comparative analysis between fresh and traditional processing samples, providing a basis for post-harvest processing in the AR production areas.